THE EFFECT OF DISSOLVED MAGNESIUM ON DIFFUSION CREEP IN CALCITE - Herwegh M.; Xiao X.; Evans B. (My University, 2003)
We experimentally tested a series of synthetic calcite marbles with varying amounts of dissolved magnesium in a standard triaxial deformation machine at 300 MPa confining pressure, temperatures between 700 and 850°C, stresses between 2 and 100 MPa, and strain rates between 10-7 and 10-3 s-1. The samples were fabricated by hot isostatic pressing of a mixture of calcite and dolomite at 850°C and 300 MPa. The fabrication protocol resulted in a homogeneous, fine-grained high-magnesian calcite aggregate with minimal porosity and with magnesium contents between 0.07 and 0.17 mol% MgCO3. At stresses below 40 MPa the samples deformed with linear viscosity that depended inversely on grain size to the 3.26+/-0.51 power, suggesting that the mechanisms of deformation were some combination of grain boundary diffusion and grain boundary sliding. Because small grain sizes tended to occur in the high-magnesium calcite, the strength also appeared to vary inversely with magnesium content. However, the strength at constant grain size does not depend on the amount of dissolved magnesium, and thus, the impurity effect seems to be indirect. At stresses higher than 40 MPa, the aggregates become non-linearly viscous, a regime we interpret to be dislocation creep. The transition between the two regimes depends on grain size, as expected. The activation energy for diffusion creep is 200+/-30 kJ/mol and is quite similar to previous measurements in natural and synthetic marbles deformed at similar conditions with no added magnesium.
Keywords: CALCITE; DIFFUSION CREEP; SOLID SOLUTION IMPURITIES; DEFORMATION MECHANISM